THE BALANCE OF PAYMENTS: AN ACCOUNTING ANALYSIS. - Farman, Wilson L.; Hou, Chi-Ming (The Accounting Review, 1963)
This article presents an accounting analysis of balance of payments. There are many problems in the field of accounting specifically, the application of the principles of double-entry and of debit and credit has been especially unsatisfactory. Moreover, accounting wise, there are many gaps; the treatment is incomplete. That is to say, there is need for someone to define carefully the accounting unit; provide an out-line of the applicable classification of accounts; discuss the similarities and contrasts between business accounting and balance-of-payments accounting and to emphasize the cautions needed in the interpretation of balance-of-payments statements. This paper is an attempt on the part of the authors-to correct the above shortcomings. In accordance with the U.S. Department of Commerce, a balance of payments is defined here as a statistical tabulation of economic transactions for a given period, between residents of one country and residents of the rest of the world.